2015
DOI: 10.1016/j.cplett.2014.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-glycine revisited: Resolving the discrepancy between theory and experiment

Abstract: Energies of 20 conformers of the Tyr-Gly dipeptide were computed using DSD-PBEP86-D3BJ/aug-cc-VTZ, with geometries from M06-2X/6-31+G* and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…As the global free energy minima of WG and WGG at 300 K match the experimental results 9 , it is suggested that the high population structures at about 300 K might have approximately been kept during the supersonic cooling process 20 . Similar result is also found recently on the IR spectra of YG conformers (Y = tyrosine) 21 . However, the number of conformations predicted by the free energy consideration is substantially more than that observed experimentally.…”
Section: Introductionsupporting
confidence: 91%
“…As the global free energy minima of WG and WGG at 300 K match the experimental results 9 , it is suggested that the high population structures at about 300 K might have approximately been kept during the supersonic cooling process 20 . Similar result is also found recently on the IR spectra of YG conformers (Y = tyrosine) 21 . However, the number of conformations predicted by the free energy consideration is substantially more than that observed experimentally.…”
Section: Introductionsupporting
confidence: 91%
“…Interestingly, the need of performing thermal corrections was emphasized in a recent study of the Tyr-Gly dipeptide. 229 While the most stable conformer was a folded and H-bonded one at 0 K, thermal corrections at 400 K made non-H-bonded conformers more stable. This finding was in accordance with spectroscopic results, which did not find any H-bonded conformers.…”
Section: Applicationsmentioning
confidence: 95%
“…Also, it was shown that the ranking of conformers differed on the free energy surface from the ranking on the PES, pointing out the importance of free energy analysis (via, for example, thermal corrections from statistical thermodynamics). Interestingly, the need of performing thermal corrections was emphasized in a recent study of the Tyr-Gly dipeptide . While the most stable conformer was a folded and H-bonded one at 0 K, thermal corrections at 400 K made non-H-bonded conformers more stable.…”
Section: Applicationsmentioning
confidence: 99%
“…Modern quantum-mechanical (QM) computations provide a much more accurate description of potential energy surfaces compared to the available RNA FFs . Unfortunately, the applicability of accurate QM methods is limited to single-point calculations and geometry optimizations of moderately sized biomolecules up to a few hundred atoms. , QM single-point energies suffer from the lack of conformational sampling for highly flexible molecules, which hinders the calculation of free energies and enthalpies. Furthermore, widely applied continuum solvation models lack specific solvent–solute interactions that are known to influence the solute geometry to various degrees. , Nevertheless, QM computations of complete nucleic acid building blocks were proven to be a viable tool for supporting the interpretation of MD simulations and identifying potential pitfalls of the FF description. …”
Section: Introductionmentioning
confidence: 99%